Antennal Transcriptome Screening and Identification of Chemosensory Proteins in the Double-Spine European Spruce Bark Beetle, Ips duplicatus (Coleoptera: Scolytinae) - Johny, Jibin; Große-Wilde, Ewald; Kalinová, Blanka; Roy, Amit (International journal of molecular sciences, 2024)
The northern bark beetle, Ips duplicatus, is an emerging economic pest, reportedly infesting various species of spruce (Picea spp.), pine (Pinus spp.), and larch (Larix spp.) in Central Europe. Recent climate changes and inconsistent forest management practices have led to the rapid spread of this species, leaving the current monitoring strategies inefficient. As understanding the molecular components of pheromone detection is key to developing novel control strategies, we generated antennal transcriptomes from males and females of this species and annotated the chemosensory proteins. We identified putative candidates for 69 odorant receptors (ORs), 50 ionotropic receptors (IRs), 25 gustatory receptors (GRs), 27 odorant-binding proteins (OBPs), including a tetramer-OBP, 9 chemosensory proteins (CSPs), and 6 sensory neuron membrane proteins (SNMPs). However, no sex-specific chemosensory genes were detected. The phylogenetic analysis revealed conserved orthology in bark beetle chemosensory proteins, especially with a major forest pest and co-habitant, Ips typographus. Recent large-scale functional studies in I. typographus chemoreceptors add greater significance to the orthologous sequences reported here. Nevertheless, identifying chemosensory genes in I. duplicatus is valuable to understanding the chemosensory system and its evolution in bark beetles (Coleoptera) and, generally, insects.
Keywords: Male; brouci; Animals; receptory pachové; stanovení celkové genové exprese; antennal transcriptome; tykadla členovců; Receptors, Odorant; mužské pohlaví; Female; Insect Proteins; Coleoptera; hmyzí proteiny; olfaction; orthologs; ženské pohlaví; bark beetles; zvířata; fylogeneze; chemosensory proteins; Transcriptome; Gene Expression Profiling; transkriptom; RNAseq; tetramer OBP; Phylogeny; Ips duplicatus; Arthropod Antennae